Change leader : learning to do what matters most - Fullan, Michael (San Francisco, CA. : Jossey-Bass/Wiley, 2011)
'Leadership expert Michael Fullan reveals six core practices for today's leaders. In his previous best-selling books, Michael Fullan examined the concepts and processes of change. Now he turns his focus to the core practices of leadership that are so vital for leading in today's complex world. He outlines the six practices-Earn Trust, Fine-Tune Focus, Develop Others, Know Your Impact, Embrace Complexity, and Hope No Matter What-which appear to be deceptively simple but actually get to the essence of what differentiates a powerful leader from one who is merely competent. Fullan argues that powerful leaders have built bedrocks of credibility, have learned how to identify the few things that matter most, and know how to leverage their skills in ways that benefit their entire organization. Provides a much-needed leadership guide for today's turbulent climate. Includes illustrative examples from business, education, nonprofit, and government sectors The author shows leaders how to eschew policies and strategies that focus on shallow and short-term goals and develop leadership skills for long-term success'--
Practice drives theory: doing is the crucible of change -- Be resolute: act with purpose and empathy -- Motivate the masses: experiencing is believing -- Collaborate to compete: multiply capacity and win -- Learn confidently: change requires confidence (but true confidence requires humility) -- Know your impact: drowning in data, thirsty for knowledge -- Sustains simplexity: just right simple.
Includes bibliographical references and index.
Keywords: Leadership; Organizational change